Studies on Corrosion Inhibition of Musa acuminata Flower Extract on Mild Steel in Acid Medium - Gunavathy, N.; Murugavel, S.C. (Asian Journal of Chemistry, 2012)
The inhibition effect of acid extract of Musa acuminata flower (MAF) on the corrosion of mild steel in 1 N hydrochloric acid solution has been investigated by potentiodynamic polarization, electrochemical impedance spectroscopy and weight loss methods. The corrosion inhibition efficiency increases with increasing flower extract concentration. Cathodic and anodic polarization curves showed that the Musa acuminata flower is a mixed type inhibitor. The effect of temperature on the corrosion behaviour of mild steel in 1 N HCl in the absence and presence of flower extract was studied in the temperature range of 30-80 ºC. Thermodynamic consideration reveals that the adsorption of Musa acuminata flower extract on mild steel surface is spontaneous and followed Langmuir and Temkin adsorption isotherms. The weight loss measurement results were close to electrochemical studies. A possible mechanism for the inhibition behaviour of flower extract by physical adsorption of its phytochemical components on the surface of the metal has been proposed.